Ablation of interleukin-19 improves motor function in a mouse model of amyotrophic lateral sclerosis - Hiroyasu Komiya; Hideyuki Takeuchi; Yuki Ogawa; Kosuke Suzuki; Akihiro Ogasawara; Keita Takahashi; Yasu-Taka Azuma; Hiroshi Doi; Fumiaki Tanaka (Molecular Brain, 2021)
Abstract Neuroinflammation by activated microglia and astrocytes plays a critical role in progression of amyotrophic lateral sclerosis (ALS). Interleukin-19 (IL-19) is a negative-feedback regulator that limits pro-inflammatory responses of microglia in an autocrine and paracrine manner, but it remains unclear how IL-19 contributes to ALS pathogenesis. We investigated the role of IL-19 in ALS using transgenic mice carrying human superoxide dismutase 1 with the G93A mutation (SOD1G93A Tg mice). We generated IL-19–deficient SOD1G93A Tg (IL-19−/−/SOD1G93A Tg) mice by crossing SOD1G93A Tg mice with IL-19−/− mice, and then evaluated disease progression, motor function, survival rate, and pathological and biochemical alternations in the resultant mice. In addition, we assessed the effect of IL-19 on glial cells using primary microglia and astrocyte cultures from the embryonic brains of SOD1G93A Tg mice and IL-19−/−/SOD1G93A Tg mice. Expression of IL-19 in primary microglia and lumbar spinal cord was higher in SOD1G93A Tg mice than in wild-type mice. Unexpectedly, IL-19−/−/SOD1G93A Tg mice exhibited significant improvement of motor function. Ablation of IL-19 in SOD1G93A Tg mice increased expression of both neurotoxic and neuroprotective factors, including tumor necrosis factor-α (TNF-α), IL-1β, glial cell line–derived neurotrophic factor (GDNF), and transforming growth factor β1, in lumbar spinal cord. Primary microglia and astrocytes from IL-19−/−/SOD1G93A Tg mice expressed higher levels of TNF-α, resulting in release of GDNF from astrocytes. Inhibition of IL-19 signaling may alleviate ALS symptoms.